Reasoning by name according to jurists: Fundamental Study - Alnasyan, Yazeed Ahmed (Journal of Islamic Sciences, 2019)
This research aimed to find out the authenticity of the name _as an abstract_ according to jurists. Can the language be vested in God’s law? Through reference to the jurists sources. In order for this research to reach its result, it took note of the definition of “Reason” and “Name” with their sections as well as differentiation between reasoning by name and similar issues, such as (Reasoning by Incomplete Reason), (Analogies in Languages), (Work by Generality), (The nickname Concept). The researcher concluded: • reasoning by name is not authentic. • alleged consensuses are rescinded by the variance represented for them. • even though (Reasoning by Name) differs from (Work by Generality), (The nickname Concept) and similar issues by conceptualization, the jurists application indicates that if they ever made a reasoning by name, they don’t mean the term written in this thesis. • the issues of “Prejury” do not fall under the term: (Reasoning by Name), and some of the issues of “Changing” fall under (Reasoning by Name) term while some do not, Finally, the issues of “Adequancy of the Less Definite” all fall under (Reasoning by Name) term.